The Impact of Implementing the Concept of Time Management in Algerian University Libraries A Field Study at the Central Library of Emir Abdelkader University, Constantine - sridi, abdelhamid (Journal of Social Sciences and Humanities, 2024)
This study aims to find out the reality of the application of time management in the library of Prince Abdelkader University, by identifying the views of library staff on organisational issues and human tendencies, with the aim of knowing the impact of these factors on the application of the concept of time management for library staff. According to the nature of the study, the descriptive method was used, where the field study included a purposive sample of 49 employees in the library, and the study concluded that organisational issues affect the good application of time management while the human tendencies factor affects relatively, and therefore the application of time management in the library of Prince Abdulkader University is relative, requiring the development of strong organisational methods.